2012
DOI: 10.1039/c2jm16555d
|View full text |Cite
|
Sign up to set email alerts
|

Role of chelate complexes in densification of CuInSe2 (CIS) thin film prepared from amorphous Cu–In–Se nanoparticle precursors

Abstract: CuInSe 2 (CIS) absorber layers for thin film solar cells were fabricated via a non-vacuum route using amorphous Cu-In-Se nanoparticle precursors prepared by a low temperature colloidal process within one minute of reaction without any external heating. In particular, we intentionally added a chelating agent to the nanoparticle colloid in order to increase the density of the final films by enhancing the viscous flow of precursor materials during high temperature selenization. This is based on the decreased reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Nevertheless, due to the high melting temperature of crystalline particles, they might not be necessarily the best choice for device fabrication. Ahn et al 121,122 reported the synthesis and utilization of amorphous Cu-In-Se nanoparticles, aiming to benet from the lower melting temperatures of such particles to assist an effective sintering during a post-thermal treatment. CuInSe 2 lms formed from amorphous Cu-In-Se nanoparticles showed dense morphologies for particles modied by chelate complexation with ethanolamine.…”
Section: Deposition From Particulate-based Solutionsmentioning
confidence: 99%
“…Nevertheless, due to the high melting temperature of crystalline particles, they might not be necessarily the best choice for device fabrication. Ahn et al 121,122 reported the synthesis and utilization of amorphous Cu-In-Se nanoparticles, aiming to benet from the lower melting temperatures of such particles to assist an effective sintering during a post-thermal treatment. CuInSe 2 lms formed from amorphous Cu-In-Se nanoparticles showed dense morphologies for particles modied by chelate complexation with ethanolamine.…”
Section: Deposition From Particulate-based Solutionsmentioning
confidence: 99%
“…The chelating effect of MEA in the hybrid ink is easily observed by the visible color change of the solution in hybrid inks. 3,15,16 A clear solution was obtained for the hybrid ink lacking MEA, but the solution turned blue when MEA was included. From the ICP elemental analysis, 1.88% of Cu was detected in the hybrid ink solution with MEA following the precipitation of Cu-Se nanoparticles; however, no Cu was detected in the hybrid ink without MEA following Cu-Se nanoparticle precipitation.…”
Section: Selection Of a Chelating Agent And Characterization Of The C...mentioning
confidence: 99%
“…[1][2][3] To date, III-V NCs including PbS, 4 PbSe 5 and PbS x Se 1Àx (ref. On the other hand, solar cells based on sintering NCs such as CuInS 2 , 7 CuInSe 2 8 and CdTe [9][10][11][12][13][14][15] have also been investigated and good device performances have been obtained. On the other hand, solar cells based on sintering NCs such as CuInS 2 , 7 CuInSe 2 8 and CdTe [9][10][11][12][13][14][15] have also been investigated and good device performances have been obtained.…”
Section: Introductionmentioning
confidence: 99%